The Influence of Work Environment and Job Training on Teacher Productivity and Its Implications for Strengthening Students' IMTAQ and IPTEK (Case Study: Islamic Center Vocational High School, Central Sulawesi) - Muhammad J. Wartabone (Publikasi Indonesia, 2025)
The rapid development of science and technology (ICT) in the modern era has significantly influenced the field of education. While this progress provides opportunities for younger generations to acquire various competencies, it also presents challenges in maintaining spiritual values, particularly in Islamic-based schools. This study investigates the influence of work environment and training on teacher productivity and examines their implications for strengthening faith and piety (IMTAQ) as well as mastery of science and technology (IPTEK) among students at the Islamic Center Vocational High School, based on a pesantren system in Central Sulawesi. The research employed a quantitative design with descriptive and associative approaches. Data were collected from 60 teachers using a saturated sampling method, and the analysis was conducted through Partial Least Square–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software. The findings revealed that the work environment had a positive and significant effect on strengthening IMTAQ and IPTEK but did not significantly affect teacher productivity. Similarly, training significantly improved the strengthening of IMTAQ and IPTEK but showed no significant effect on teacher productivity. Teacher productivity, however, was found to significantly enhance the strengthening of IMTAQ and IPTEK. The moderating effects of teacher productivity combined with both work environment and training did not demonstrate a significant influence on IMTAQ and IPTEK reinforcement. These results highlight the importance of designing effective training programs and providing a conducive work environment that not only enhances productivity but also supports holistic educational goals, integrating spiritual values with scientific and technological competence.